Metano entérico de bovinos leiteiros em condições tropicais brasileiras - Primavesi, Odo; Shiraishi Frighetto, Rosa Toyoko; Pedreira, Márcio Dos Santos [UNESP]; De Lima, Magda Aparecida; Berchielli, Telma Teresinha [UNESP]; Barbosa, Pedro Franklin (FapUNIFESP (SciELO), 2004)
The objective of this work was to quantify methane (CH4) emission using the sulfur hexafluoride (SF6) tracer technique, by dairy cattle on pasture in Brazilian tropical field conditions. Measurements were performed in the rainy season, with Holstein and Holstein x Zebu crossbred, from lactating and dry cows and heifers grazing fertilized Tobiatã grass, and heifers grazing unfertilized Brachiaria grass. Methane and SF6 concentrations were determined by gas chromatograph. Methane emissions by lactating cows varied from 13.8 to 16.8 g/hour, by dry cows from 11.6 to 12.3 g/hour, by heifers grazing fertilized grass was 9.5 g/hour and by heifers grazing unfertilized grass varied from 7.6 to 8.3 g/hour or 66 to 72 kg/head/year. Methane emission per digestive dry matter intake (DMDI) varied from 42 to 69 g/kg DMDI for lactating cows, 46 to 56 g/kg for dry cows, 45 to 58 g/kg for heifers grazing fertilized grass and 58 to 62 g/kg for heifers in unfertilized grass pasture. The CH4 emission measured on dairy cattle feeding tropical grasses was higher than that observed for temperate climate conditions.

O objetivo deste trabalho foi quantificar a taxa de emissão de metano (CH4) pela técnica do gás traçador, hexafluoreto de enxofre (SF6), em bovinos leiteiros a pasto em condições tropicais brasileiras. As medições foram realizadas na estação das chuvas, com adequada oferta de forragem, em animais da raça Holandesa e Mestiça Leiteira Brasileira em pastagem de capim-tobiatã (Panicum maximum Jacq. cv. Tobiatã) adubada, com vacas em lactação, vacas secas e novilhas, e em pastagem de capim-braquiária (Brachiaria decumbens Stapf.) não adubada com novilhas. As concentrações de CH4 e SF6 foram determinadas por cromatografia gasosa. A emissão de CH4 pelas vacas em lactação foi de 13,8 a 16,8 g/hora, pelas vacas secas de 11,6 a 12,3 g/hora, pelas novilhas em pastagem adubada de 9,5 g/hora, e pelas novilhas em pastagem sem adubo de 7,6 a 8,3 g/hora ou 66 a 72 kg/animal/ano. A emissão de CH4 por matéria seca digestiva ingerida foi de 42 a 69 g/kg em vacas em lactação, de 46 a 56 g/kg em vacas secas, 45 a 58 g/kg em novilhas ingerindo pasto adubado e 58 a 62 g/kg em novilhas em pastagem sem adubo. A emissão de CH4 por bovinos leiteiros ingerindo gramíneas tropicais é superior à emissão por bovinos ingerindo gramíneas de clima temperado.
Dairy cattle enteric methane measured in Brazilian tropical conditions
Keywords: Greenhouse gas; Internal tracer; Ruminal methane; Sulfur hexafluoride; Bos indicus; Bos taurus; Brachiaria; Poaceae